Interaction between C-Reactive Protein and Endothelin-1 in Coronary Artery Disease - FAK, ALİ SERDAR; TOKAY TARHAN, SENA (KARGER, 2007)
Background: Increased concentrations of serum C-reactive protein (CRP) have been reported to predict major cardiovascular events in patients with coronary artery disease (CAD). Increased concentrations of endothelin-1 (ET-1) are also associated with poor prognosis after myocardial infarction. Hypothesis: We tested the hypothesis that ET-1 might contribute to CRP in prediction of adverse outcome in CAD. Methods: Serum high sensitive CRP and plasma ET-1 levels of 40 patients who have stable CAD and 25 control subjects were measured, and correlation analysis between these molecules was performed. Results: Mean high sensitive CRP was 8.64 +/- 12.73 mg/l, and mean ET-1 was 8.24 +/- 7.06 pg/ml in the CAD group. We found that there was no statistically significant correlation between high sensitive CRP and ET-1 in either CAD group (p = 0.82), or the control group (p = 0.85). In a subgroup of 13 patients who were not under statin treatment, we found a strong correlation between the levels of these molecules (p = 0.01). Conclusion: Our study does not clearly support or exclude a link between CRP and ET-1 in patients who have stable CAD. Copyright (C) 2007 S. Karger AG, Basel
Keywords: Atherosclerosis; Coronary artery disease; C-reactive protein; Endothelin-1; Statin